THEME AND RHEMEON STUDENTS’ WRITING WITH DIFFERENT OBJECTS - Thia Ananda; Siti Aisah Ginting; Juli Rachmadani Hasibuan (Universitas Negeri Medan, 2019)
The objective of this study were to find out the dominant types of Theme and Rheme used in students’ writing in Science and Social Class and to describe the Theme and Rheme realized in students’ writing in Science and Social Class. Theme is what the writer taking about and rheme was this was what writer saying about and common used in the text. This study was conducted by using descriptive qualitative design. The subject of this study was students’ writing of Recount Text from tenth grade of Science and Social class in SMA Kartika 1-2 Medan. The data were collected from the students’ writing. From the research, it was found all the kinds of theme: topical, textual, interpersonal, marked and unmarked theme were found. And the most dominant kind of theme was marked theme and topical theme.The Theme realization pattern were found in students’ writing of recount text in both Science and Social class namely, topical theme, textual-topical theme and interpersonal-topical theme. While topical-textual-interpersonal was occured in this research simultaneously.Keywords: Theme and Rheme, Students’ Writing, Different Objects.